Liz's Effort To Get Better Life In Breaking Night Novel (2010): An Individual Psychological Approach - Andari, Ovi Ariesta Ayu; , Drs. Abdillah Nugroho, M. Hum; , Titis Setyabudi, S.S. M. Hum (2014)
The problem of this study is Liz's effort to get better life in breaking night Novel (2010) directed by Liz Murray. The purpose of this study was to describe the novel based on the structural elements and depict the novel based on individual psychological approach. The type of this research is qualitative research. This type of research data is a text taken from two data sources: primary and secondary. The primary data source is The breaking night novel by author Liz Murray in 2010. While secondary data sources are other materials taken from some books, author biographies, comments, website searching about breaking night novel. Both the data collected by conducting library research and analyzed with descriptive analysis. Based on the analysis, the author describes some conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, plot, setting, point of view, style, theme. Secondly, based on individual psychological analysis reflected in striving for superiority, fictional finalism, inferiority feeling, social interest, style of life, creative power all of this have meaningful goal in human's life. This novel also shows the determination process involving large will produce amazing results.